2013
DOI: 10.1016/j.rdc.2012.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Disease Management

Abstract: Osteoarthritis is the most prevalent chronic joint disease worldwide. The incidence and prevalence are increasing as the population ages and lifestyle risk factors such as obesity increase. There are several evidence-based clinical practice guidelines available to guide clinician decision making, but there is evidence that care provided is suboptimal across all domains of quality: effectiveness, safety, timeliness and appropriateness, patient-centered care, and efficiency. System, clinician, and patient barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 98 publications
1
18
0
1
Order By: Relevance
“…This renders the guidance less useful and decreases the potential impact of research studies on clinical practice. Indeed, studies suggest that the uptake and use of clinical guidelines in daily practice are suboptimal 19,20 , possibly attributable to the lack of specificity of the recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…This renders the guidance less useful and decreases the potential impact of research studies on clinical practice. Indeed, studies suggest that the uptake and use of clinical guidelines in daily practice are suboptimal 19,20 , possibly attributable to the lack of specificity of the recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…Suboptimal care has been demonstrated across a number of quality domains including provision of effective treatments, safety, access to educational material and support for self-management. 22 For example, the Australian CareTrack study showed that only 43% of people with OA received recommended care. 20 In particular, non-drug, non-surgical interventions are not given the importance by GPs that is recommended by all CPGs, 15 23 24 while prescribing patterns appear to be better aligned with recommendations for pharmacological treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Physiotherapists should consider employing strategies that assist people to begin and sustain new behaviours that improve their osteoarthritis (Bassett, 2015). Furthermore, as osteoarthritis is a chronic disease, treatment should be viewed as a continuum of care; hence, booster sessions should be considered to assist in the maintenance of regular exercise (Brand, Ackerman, Bohensky, & Bennell, 2013;Rosemann, Laux, Szecsenyi, & Grol, 2008).…”
Section: Myth 5: Conservative Treatments Are Ineffectual and Only Desmentioning
confidence: 99%